2010
DOI: 10.1007/s12529-010-9103-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Associations among Overtime Work, Health Behaviors, and Health: A Longitudinal Study among Full-time Employees

Abstract: BackgroundIt has often been suggested that high levels of overtime lead to adverse health outcomes. One mechanism that may account for this association is that working overtime leads to elevated levels of stress, which could affect worker’s behavioral decisions or habits (such as smoking and lack of physical activity). In turn, this could lead to adverse health.PurposeThe present study examined this reasoning in a prospective longitudinal design. Data from the prospective 2-year Study on Health at Work (N = 64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 26 publications
1
47
1
Order By: Relevance
“…Eleven of these (6 of the 7 studies summarised by van der Hulst, 2003;Albertsen et al, 2004;Mizoue et al, 2006;Lallukka et al, 2008;Taris et al, 2011;Macy et al, 2013) found no clear relationship between long working hours and smoking behaviour. All of these studies were based on between-person analysis.…”
Section: Comparisons With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven of these (6 of the 7 studies summarised by van der Hulst, 2003;Albertsen et al, 2004;Mizoue et al, 2006;Lallukka et al, 2008;Taris et al, 2011;Macy et al, 2013) found no clear relationship between long working hours and smoking behaviour. All of these studies were based on between-person analysis.…”
Section: Comparisons With Previous Studiesmentioning
confidence: 99%
“…They found that working long hours (41 hours or more a week) had no impact on smoking cessation. Taris et al (2011) examined the relationship between harmful behaviours (an index based on the combined intensity of smoking and alcohol consumption) and overtime working. They found no relationship between an increase in harmful behaviour and the number of overtime hours worked among a sample of 649 full-time employees in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…There are several factors that are associated with overtime work, from socioeconomic factors to individual coping behaviors. Tairs et al tested whether overtime work affected workers' health behaviors in their two-wave prospective study [3]. Their hypotheses were partially supported.…”
mentioning
confidence: 99%
“…One study by Taris et al [26] examined the relationships between overtime, health behaviours and health outcomes to determine the mechanism behind these factors. The authors reported that higher overtime was associated with less health protective behaviours and lower subjective health.…”
mentioning
confidence: 99%
“…It is likely that nutrition, physical activity and sleep are the primary behaviours negatively influenced by excess hours spent at work because they require the most conscious effort by an individual. These behaviours should be the target of future health promotion efforts [26].…”
mentioning
confidence: 99%